Nanotherapy: Nanotherapy in Joints: Increasing Endogenous Hyaluronan Production by Delivering Hyaluronan Synthase 2 (Adv. Mater. 46/2019). Issue 46 (12th November 2019) - Li, Huimin; Guo, Huilin; Lei, Chang; Liu, Li; Xu, Liqin; Feng, Yaping; Ke, Jin; Fang, Wei; Song, Hao; Xu, Chun; Yu, Chengzhong; Long, Xing
Abstract : In article number 1904535, Chun Xu, Chengzhong Yu, Xing Long, and co‐workers report a new strategy to promote endogenous production of hyaluronic acid for the management of osteoarthritis by delivering hyaluronan synthase type 2 into the synoviocytes of joints using biodegradable mesoporous silica nanoparticles. This nanotherapy also helps in the repair of bone defects in a rat osteoarthritis bone‐defect model.